2009
DOI: 10.1371/journal.pone.0005617
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2-Aminothiazole-4-Carboxylate Derivatives Active against Mycobacterium tuberculosis H37Rv and the β-Ketoacyl-ACP Synthase mtFabH

Abstract: BackgroundTuberculosis (TB) is a disease which kills two million people every year and infects approximately over one-third of the world's population. The difficulty in managing tuberculosis is the prolonged treatment duration, the emergence of drug resistance and co-infection with HIV/AIDS. Tuberculosis control requires new drugs that act at novel drug targets to help combat resistant forms of Mycobacterium tuberculosis and reduce treatment duration.Methodology/Principal FindingsOur approach was to modify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 28 publications
2
46
0
Order By: Relevance
“…Moreover, as observed for the smaller acyl substituents at C3 (compounds 5 and 6), a keto group with larger substituents (compounds 7-11) resulted in improved binding affinities with both the free enzyme and the acyl mimic. In addition, compounds with larger, more hydrophobic groups were generally found to have higher affinity for wild-type and C171Q KasA enzymes, in agreement with previous studies in which lipophilicity was identified as a key feature of KAS inhibitor design (7)(8)(9). For example, ethyl-chlorophenyl analog compound 12 had K d and K i values of 128 and Ͼ 400 M, respectively, whereas butyl-chlorophenyl analog compounds 15 had K d and K i values of 68 and 77 M, respectively.…”
Section: Conflictingsupporting
confidence: 89%
“…Moreover, as observed for the smaller acyl substituents at C3 (compounds 5 and 6), a keto group with larger substituents (compounds 7-11) resulted in improved binding affinities with both the free enzyme and the acyl mimic. In addition, compounds with larger, more hydrophobic groups were generally found to have higher affinity for wild-type and C171Q KasA enzymes, in agreement with previous studies in which lipophilicity was identified as a key feature of KAS inhibitor design (7)(8)(9). For example, ethyl-chlorophenyl analog compound 12 had K d and K i values of 128 and Ͼ 400 M, respectively, whereas butyl-chlorophenyl analog compounds 15 had K d and K i values of 68 and 77 M, respectively.…”
Section: Conflictingsupporting
confidence: 89%
“…In strategy A, we took advantage of the high homology between PqsD and the β-ketoacyl-acyl carrier protein synthase III. Hence, seven described FabH inhibitors were selected as starting points for the development of PqsD inhibitors (Figure 2A) [20][21][22][23][24][25]. After synthesis of additional derivatives compounds A1-A12 were tested for in vitro activity.…”
Section: For Reprint Orders Please Contact Reprints@future-sciencecommentioning
confidence: 99%
“…2-Aminothiazole moieties are useful structural motifs in medicinal chemistry as they have been reported to possess antitumor, 2 antiviral, 3,4 antibacterial, [5][6][7] anti-prion, 8 psychotropic, anti-allergic, 10 anti-hypertensive, 11 anti-inammatory, 12,13 antifungal, 14 antitubercular, 15 anti-HIV, 16 pesticidal, 17 antiprotozoal, 18 antipyretic, 19 antioxidative, 20 and analgesic 21 activities. Aminothiazoles acts as ligands of estrogen receptors 22 and represent a novel class of adenosine receptor antagonists; 23 its other analogues are used as fungicides, inhibiting the in vivo growth of Xanthomonas, and as an ingredient of herbicides or as schistosomicidal and anthelmintic drugs.…”
Section: Introductionmentioning
confidence: 99%